Sigurnost i zaštita na nogometnim utakmicama i ostalim sportskim priredbama prema rješenjima konvencije Vijeća Europe CETS br. 218 - Primorac, Damir, pravnik (Array, 2019)
Encouraged by the violent behavior of certain football fans in Brussels at Heysel Stadium on 29 May 1985, the Council of Europe European Convention on Spectator Violence and Misbehaviour at Sports Events and in particular at Football Matches i.e. Convention no. 120 (CETS no. 120) which entered into force on 1 November 1985. Convention no. 120 retained its original features until 2013 when the Council of Ministers concluded that it was outdated and that it was not in line with the experience gained since the entry into force. Consequently, the Standing Committee decided to draft a new text of the Convention and it resulted with Convention no. 218 (CETS no. 218) i.e. Council of Europe's Convention on an Integrated Safety, Security, and Service Approach at Football Matches and Other Sports Events. Safety measures, security measures and measures in the area of services, as a key part of Convention No. 218, aim to create a safe and secure environment at all sports events. An integrated approach to safety and security requires coordination at the international, national and local levels, and emphasizes the importance of effective co-operation with the police, emergency services and other partners not only in terms of guaranteeing physical security but also in preventing discriminatory and racist behavior. The importance of establishing a national football information point has also been established as a key mediator in the exchange of information on football matches with an international character as well as for the international cooperation of state bodies essential for the safety and security at football matches. Reasons for the emergence of Convention no. 218 is not only in the prevention of violent behavior at sporting events and in improving safety and security, but also in further development and better coordination of international cooperation in the prosecution of perpetrators of such inappropriate acts.